A river health assessment of selected Southwestern Cape rivers : riparian vegetation index (RVI) application, evaluation and alternatives - Withers, Melanie Jane (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2003.